Auguste Comte dan Kontribusinya terhadap Kajian Sosiologi Dakwah: Auguste Comte dan Kontribusinya terhadap Kajian Sosiologi Dakwah - Alfiansyah Anwar; Musafir Pababbari; Nila Sastrawati; Musdalifa Ibrahim (SOSIOLOGIA : Jurnal Agama dan Masyarakat, 2023)
The sociology of da'wah is a field of science that studies social interaction in the context of the spread of religion and da'wah. In its development, the contribution of an important figure in sociological thinking became very significant. One of the figures who made a major contribution to the study of the sociology of preaching was Auguste Comte. One of the main concepts put forward by Auguste Comte was the three-stage concept of law. This research basically aims to provide in-depth insight and a wider understanding of the relationship between sociology and da'wah or the relationship between society and the spread of Islam, as well as the importance of using scientific methods in analyzing the role of da'wah in society. This research uses a library method with a library study approach, by collecting data from reading books, articles from journals, the internet, or other written literature as a basis for writing in this research. The findings in this research refer to Auguste Comte's law of three stages, namely: The first stage is the "theological stage", preachers at this stage use religious beliefs and explanations of supernatural powers in spreading religious teachings to society. The second stage “metaphysical stage” marks the transition from explanations of supernatural powers to more abstract explanations. Preachers at this stage use a more rational approach and are based on philosophical thinking to explain and preach about the Islamic religion to the public. And the third "positive stage" is a transition from rational philosophical-based explanations, which are more rational or scientific. Preachers at this stage use a scientific approach in preaching to spread the religion of Islam. The preachers explain and analyze the impact of religion on social life, the relationship between religion and political, economic, cultural power and the dynamics of social change related to religion